"Monitoria é tirar dúvida, não é dar aula": significações construídas em um programa de monitoria de uma universidade federal brasileira sob a perspectiva do construcionismo social - Vieira, Lucas Rocha (2019)
This work sought to understand how the meanings and senses attributed to the monitorship, by the university, by the instructors and monitors imply the organization of the daily life of those involved, generating contributions and limitations. In addition, it is argued that it is important for monitorship to have a formative sense. Thus, the study was guided by three questions: What are the meanings and senses attributed to academic monitorship by university, teachers and monitors? How do these significations imply the organization of daily monitoring? How does this monitoring routine provide contributions or limitations to the participants? For that, a literature review was presented that dealt with the monitoring in higher education, the formative sense of this activity and the teacher initiation for the higher education. In order to understand these questions, the work had its theoretical-methodological foundation in Social Constructionism, as presented by Spink (2010, 2013), which uses mainly Berger and Luckmann productions (1976); Gergen (1995) and Bakhtin (1994a; 1994b; 1995). In relation to the methodological procedures, it is a basic qualitative study, whose unit of analysis was a didactic-scientific department of a Brazilian University. Data were collected through documentary research and qualitative interviews with 12 monitors, 8 guidance teachers and 5 members of the Monitoring Program Monitoring Committee. And they were analyzed using the method of analysis of discursive practices proposed by Spink (2013). The results were discussed as the perception about the objectives of the program, the activities carried out by the monitors and the senses attributed to the monitoring form a fabric of meanings where it was monitored as a session to "ask questions" of the students. This sense is mobilized in the daily organization of the monitoring in relation to the place where the activities of the monitor are carried out, the orientation offered to the monitors, the conception attributed to the monitoring as initiation to teaching, and the expected characteristics of the monitor. From this quotidian we observed several contributions of the monitoring to the academic community, but also limitations in the realization of its formative potential.